2007
DOI: 10.1590/s0100-879x2007000200014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polymorphism at site -174 G/C of interleukin-6 promoter region in multiple myeloma

Abstract: It is well established that interleukin-6 (IL-6) is an essential growth factor for multiple myeloma (MM) and patients with increased IL-6 levels have a poor prognosis. In healthy subjects, the presence of the C allele at a polymorphic site (-174 G/C) of the IL-6 gene is related to low IL-6 levels. In view of the potential association of this particular polymorphism with IL-6 concentration, and the relevance of IL-6 in MM pathogenesis, the objective of the present study was to investigate the prevalence of IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…IL-6 is associated with poor prognosis in various malignancies (Deans et al, 2007;DeMichele et al, 2009). Nevertheless, it was reported that this cytokine was not associated with multiple myeloma or primary cutaneous melanoma (Martinez-Escribano et al, 2003;Duch et al, 2007). No data are available on a possible association with CML.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is associated with poor prognosis in various malignancies (Deans et al, 2007;DeMichele et al, 2009). Nevertheless, it was reported that this cytokine was not associated with multiple myeloma or primary cutaneous melanoma (Martinez-Escribano et al, 2003;Duch et al, 2007). No data are available on a possible association with CML.…”
Section: Discussionmentioning
confidence: 99%
“…A possible cause for the conflicts and mismatches, like those observed here and the earlier study in allele and genotype distributions, may be the differences in racial or ethnical backgrounds. Duch et al analyzed 52 patients with multiple myeloma and found that the G allele frequency was higher in the Brazilian population than in the European population (Duch C et al, 2007). Nowadays Yeh et al observations on the allele and genotype distribution of the IL-6 −174 G/C polymorphism demonstrated that there are low frequencies of the G allele and GG genotype in the Taiwanese CRC population compared to the Western counterpart (Yeh et al, 2009).…”
Section: Cytokine Gene Polymorphisms Of Proinflammatory Cytokines: Ilmentioning
confidence: 99%
“…In general, cytokine-encoding genes have been extensively investigated (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86), due to the high degree of polymorphisms characterized in these genes and to their important role in the bone marrow microenvironment and B-cell development.…”
Section: Genetic Risk Factors In Multiple Myelomamentioning
confidence: 99%
“…Several reports investigated SNPs in IL6, IL6R and IL6ST genes (75,76,(80)(81)(82) and up to date, several studies failed to evidence association with the well studied IL6 promoter -174G/C SNP (rs1800795) (70,75,(80)(81)(82). In one study the IL6 -572G/C (rs1800796) was associated with an increased risk to develop MM for carriers of the -572C allele (75).…”
Section: Genetic Risk Factors In Multiple Myelomamentioning
confidence: 99%